KINERJA PEGAWAI SEKSI KELAHIRAN DAN KEMATIAN DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN SIAK DALAM PELAYANAN PENGURUSAN AKTA KELAHIRAN - Juma’at Lubis; Harapan Tua R.F.S (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Birth Certificate is a certify document of the status and birth event of a person issued by the Birth and Death Section Population and Civil Registration of Siak Regency.The purpose of the research for the knowing the performance of the employee Birth and Death Section Population and Civil Registration Departement Siak Regency in the birth certificate accomplishment service and to know the factors that influence it.Indicators of the research is performance indicators by Hasibuan (2014:22) is: Job Achievement, Discipline, Creativity, Cooperation, Capability, and Responsibility. This research method used descriptive qualitative research type. Informations of the research is, Head of Civil and Registration, Head of Birth and Death Section, Employee of Birth and Death Section, people has accomplishment service birth certificate and people has not accomplishment service birth certificate. Technique of collecting data in this research is by interview, observation and documentation.The result of this research idicate the performance of the Employee Birth and Death Section Population and Civil Registration Departement Siak Regency in birth certificate accomplishment service is good seen froom indicator of job achievement, discipline, capability, cooperation and responsibility but still needed improvement in creativity indicator. So from that needed improvement in performance employee of Birth and Death Section Population and Civil Registration Siak Regency. So that later increasing ownership birth certificate in Siak Regency.Key Word: Performance of Employee, Birth Certificate, Birth and Death Section